The Effect of Work Overload, Organizational Commitment, and Development Career on Employee Turnover Intention - Marsyah, Ira; Widigdo, Aslam Mei Nur (Universitas Mercu Buana, 2024)
This study's goal is to ascertain and examine the impact of work overload, organizational commitment, and career development on turnover intention, using all PT Sarana Global employees as the objects. This study employed 35 respondents and a causal model in a quantitative manner. Multiple linear regression statistical analysis was also used in this study, and the data were processed using IBM SPSS 25. This study comes to the conclusion that job overload is the reason for the positive influence, which also significantly affects the intention to leave. In the meantime, organizational commitment has a major detrimental impact on turnover intentions. Aside from that, turnover intention is unaffected by career development.